2014
DOI: 10.1093/neuonc/nou160
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/randomized phase II study of afatinib, an irreversible ErbB family blocker, with or without protracted temozolomide in adults with recurrent glioblastoma

Abstract: Afatinib has a manageable safety profile but limited single-agent activity in unselected recurrent GBM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
129
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 42 publications
2
129
0
2
Order By: Relevance
“…Beyond the randomized trial leading to the approval of TMZ mentioned above, two other randomized trials with TMZ monotherapy as one of the treatment arms have been published, a direct comparison with the combination of procarbazine, lomustine and vincristine (PCV) before TMZ became first-line standard [69] and a negative trial for the epidermal growth factor recetor (EGFR) tyrosine kinase inhibitor afatinib [70] ( Table 2 and The anti-vascular endothelial growth factor (VEGF) antibody bevacizumab [72][73][74][75], interferon-α2b [76], the multikinase inhibitor sorafenib [77], O6-benzylguanine [78], irinotecan [79], cisplatin [80,81], liposomal doxorubicine [82] and ABT-414, an EGFR-targeted antibody-drug conjugate conjugated to monomethylauristatin F [83].…”
Section: Temozolomide Monotherapy and Combination Regimensmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond the randomized trial leading to the approval of TMZ mentioned above, two other randomized trials with TMZ monotherapy as one of the treatment arms have been published, a direct comparison with the combination of procarbazine, lomustine and vincristine (PCV) before TMZ became first-line standard [69] and a negative trial for the epidermal growth factor recetor (EGFR) tyrosine kinase inhibitor afatinib [70] ( Table 2 and The anti-vascular endothelial growth factor (VEGF) antibody bevacizumab [72][73][74][75], interferon-α2b [76], the multikinase inhibitor sorafenib [77], O6-benzylguanine [78], irinotecan [79], cisplatin [80,81], liposomal doxorubicine [82] and ABT-414, an EGFR-targeted antibody-drug conjugate conjugated to monomethylauristatin F [83].…”
Section: Temozolomide Monotherapy and Combination Regimensmentioning
confidence: 99%
“…Several EGFR-targeting agents have been developed, such as gefitinib, erlotinib or afatinib, a strategy effective in EGFR-mutated non-small-cell lung cancer, however, so far with disappointing results in glioblastoma [57,70,108,115].…”
Section: Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Four randomized phase II clinical trials were conducted using single-agent TMZ (127,159,166,167). A randomized trial comparing sdTMZ with procarbazine, in TMZ-naive patients, revealed a PFS6 of 21% versus 8%, with a median OS 1.5 months longer in the TMZ arm (127).…”
Section: Temozolomide Monotherapy and Combination Regimensmentioning
confidence: 99%
“…However, these trials were not conducted in biomarker-selected populations overexpressing the target. Recently, in a phase II trial in recurrent glioblastoma evaluating the ErbB family blocker afatinib, a small efficacy signal in EGFRvIII-positive tumors versus -negative tumors was seen (median PFS 3.4 versus 1.0 months) [61]. Currently tested in phase IIb/III is ABT-414, an antibody-drug conjugate targeting EGFR in its active conformation.…”
Section: Other Targeted Therapiesmentioning
confidence: 99%